Genome-Wide Identification and Expression Analysis of the BTB Domain-Containing Protein Gene Family in Sugar Beet - Qiao Yang; Yu Liu; Chunlei Zhao; Xi Wang; Guangzhou Ding; Yanli Li; Li Chen (Agronomy, 2022)
Cercospora leaf spots (CLSs) is a fungal disease of sugar beet caused by C. beticola, which damages leaves and leads to yield cut on sugar beet worldwide. BTB protein genes are critical to plant defense against bacterial infection. Here, 49 members of the BTB protein gene family were identified from the big data of the sugar beet genome, and bioinformatics was used to analyze the BTB protein family. Through molecular techniques, C. beticola of CLS was identified. In addition, the transcriptome data of sugar beet resistant and susceptible materials after C. beticola infection were obtained. Three BTB genes most significantly related to C. beticola stress were screened from the transcriptome data. The three genes are BvBTB1, BvBTB2, and BvBTB3, their full-length cDNA sequences were acquired by RT-PCR. The phenotypes of sugar beet resistant and susceptible materials under different spore concentrations of C. beticola were analyzed. Further, under the stress of C. beticola, qRT-PCR results showed that the expression levels of BvBTB1, BvBTB2, and BvBTB3 in roots and leaves were tissue-specific and expressed differently in various tissues. BvBTB1, BvBTB2, and BvBTB3 were overexpressed in the resistant and susceptible materials within five days after C. beticola infection: the peak appeared on the fifth day, and the highest expression was 25 times that of the control group. However, the lowest was 1.1 times of the control group, moreover, the expression in the resistant material was higher than that in the susceptible material. Overall, these results showed that BvBTB genes were involved in the response in sugar beet to C. beticola infection. Therefore, the study provided a scientific theoretical basis for developing new resistant varieties in sugar beet.